Phage-displayed nanobody-based fluorescence-linked immunosorbent assay for the detection of Cry3Bb toxin in corn. (15th December 2022) - Qiu, Yulou; You, Ajuan; Zhang, Mingzhou; Cui, Haifeng; Fu, Xianshu; Wang, Jianping; Huang, Haizhi; Shentu, Xuping; Ye, Zihong; Yu, Xiaoping
Abstract: Cry toxins have been widely used as biopesticides and applied in transgenic crops for the control of pests, raising public concerns for unforeseen environmental and health risks. In this study, five phage-displayed nanobodies against Cry3Bb toxin were selected from a naive nanobody library by screening. Using purified phage-displayed nanobody as capture antibody, a novel double-antibody sandwich fluorescence-linked immunosorbent assay (FLISA) based on quantum dot beads (QBs) was established for the determination of Cry3Bb toxin. The developed method exhibited a linear working range of 31.25–500 ng/mL and a low detection limit of 8.45 ng/mL. The recoveries of Cry3Bb toxin from spiked corn samples were ranging from 93.1% to 116.8% with a coefficient of variation lower than 9.4%. Molecular modeling results showed that key amino acids in the CDR3 region of nanobody P27 combine with Cry3Bb toxin through hydrogen bonds and hydrophobic interactions. These results indicated that the phage-displayed nanobody-based QBs-FLISA may provide a possible tool for detecting Cry3Bb toxin in corn. Graphical abstract: Image 1 Highlights: Phage-displayed nanobodies against Cry3Bb toxin were first obtained from a naive nanobody library. A phage-displayed nanobody-based QBs-FLISA for Cry3Bb with good sensitivity and specificity was developed. This method was successfully applied to detect Cry3Bb in corn. The binding characteristics between nanobody and Cry3Bb were analyzed by molecular simulation.